2010
DOI: 10.1080/03601231003800263
|View full text |Cite
|
Sign up to set email alerts
|

Unreliable pesticide control of the vector psyllidDiaphorina citri(Hemiptera: Psyllidae) for the reduction of microorganism disease transmission

Abstract: Systemic insecticides and application methods were examined for the control of the vector psyllid of citrus greening disease, Diaphorina citri, on grown king mandarin trees in an orchard in southern Vietnam from May 2007 to September 2008. Leaf spraying of imidacloprid, thiamethoxam, and clothianidin attained about 50 % to 70 % mortality of the psyllid for one month after the application and showed decreased efficacy thereafter. Imidacloprid was more effective than the other two insecticides, but the efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…The disease is transmitted by a small insect vector of the family Psyllidae. The growth of psyllids cannot yet be reliably controlled by conventional insecticide application (Ichinose et al, 2010). Without successful measures to control the causal pathogen and its transmission vector, HLB is endemic to a variety of citrus species and related plants.…”
Section: Introductionmentioning
confidence: 99%
“…The disease is transmitted by a small insect vector of the family Psyllidae. The growth of psyllids cannot yet be reliably controlled by conventional insecticide application (Ichinose et al, 2010). Without successful measures to control the causal pathogen and its transmission vector, HLB is endemic to a variety of citrus species and related plants.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the insecticide treatments did not reduce HLB spread compared to the untreated controls. Indeed, the insecticides commonly used for the control of the psyllid were not as effective as expected (Ichinose et al 2010), and even induced insecticide resistance in field populations of D. citri in Florida (Tiwari et al 2011). For each of the treatments, the Ct values of Las varied over time but generally decreased from November 2008 to October 2011 ( Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, secondary pest outbreaks of various citrus scales and mealy bugs can be a real threat resulting from intensive insecticide use for psyllid control (Wakgari and Giliomee 2003). In addition, the insecticides commonly used for the control of the Asian citrus psyllid have not been as effective as expected (Ichinose et al 2010). Finally, insecticides may be helpful in reducing the spread of Ca.…”
Section: Introductionmentioning
confidence: 98%
“…However, the relatively shorter residue effect would need more frequent application of the insecticide which would not be preferred by farmers. Although either imidacloprid or methidathion was not effective if they were applied on grown trees in field (Ichinose et al, 2010b), it has been reported that imidacloprid effectively control psyllid populations in field (cf. Srninivasan et al, 2008;Boina et al, 2009;Gatineau et al, 2010).…”
Section: Comparison Of Application Modementioning
confidence: 99%
“…Serious problem in the management of citrus greening by insecticides in southern Vietnam is raised in the cultivation of king mandarin, which is the most predominant cultivars in southern Vietnam. When trees grew in the stage to yield fruits, usually one and half to two years after planting, the efficacy of neonicotinoids is significantly reduced or even lost despite either the dose or the mode of application (Ichinose et al, 2010b). The control efficiency on the psyllid on grown trees was not implemented by either the increase of insecticide dose up to 100 times or the change of the application mode, not only soil drench but also trunk injection, trunk painting, or leaf spray.…”
Section: Introductionmentioning
confidence: 99%